PENGARUH DPR, DER, ROA DAN ROE TERHADAP PRICE EARNING RATIO PADA PERUSAHAAN MANUFAKTUR - Sijabat, Frengky David; Suarjaya, Anak Agung Gede (E-Jurnal Manajemen; Vol 7 No 7 (2018)DO - 10.24843/EJMUNUD.2018.v07.i07.p09, 2018)
The research has a purpose to know the influence of dividend payout ratio, debt to equity ratio, return on asset and return on equity to price earning ratio at manufacturing company listed on Indonesian stock exchange.The number of samples used are 36 companies. The analysis technique used is multiple linear regression. The result of analysis shows that Dividend Payout Ratio have positive and significant effect to Price Earning Ratio, Debt to Equity Ratio have negative and significant effect to Price Earning Ratio, Return on Asset has no effect on Price Earning Ratio, Return on Equity has positive and significant effect to Price Earning Ratio.